Dose to heart substructures is associated with non-cancer death after SBRT in stage I–II NSCLC patients. Issue 3 (June 2017) - Stam, Barbara; Peulen, Heike; Guckenberger, Matthias; Mantel, Frederick; Hope, Andrew; Werner-Wasik, Maria; Belderbos, Jose; Grills, Inga; O'Connell, Nicolette; Sonke, Jan-Jakob
Abstract: Background and purpose: To investigate potential associations between dose to heart (sub)structures and non-cancer death, in early stage non-small cell lung cancer (NSCLC) patients treated with stereotactic body radiation therapy (SBRT). Methods: 803 patients with early stage NSCLC received SBRT with predominant schedules of 3 × 18 Gy (59%) or 4 × 12 Gy (19%). All patients were registered to an average anatomy, their planned dose deformed accordingly, and dosimetric parameters for heart substructures were obtained. Multivariate Cox regression and a sensitivity analysis were used to identify doses to heart substructures or heart region with a significant association with non-cancer death respectively. Results: Median follow-up was 34.8 months. Two year Kaplan–Meier overall survival rate was 67%. Of the deceased patients, 26.8% died of cancer. Multivariate analysis showed that the maximum dose on the left atrium (median 6.5 Gy EQD2, range = 0.009–197, HR = 1.005, p -value = 0.035), and the dose to 90% of the superior vena cava (median 0.59 Gy EQD2, range = 0.003–70, HR = 1.025, p -value = 0.008) were significantly associated with non-cancer death. Sensitivity analysis identified the upper region of the heart (atria + vessels) to be significantly associated with non-cancer death. Conclusions: Doses to mainly the upper region of the heart were significantly associated with non-cancer death. Consequently, dose sparing in particular of the upper region of the heart could potentially improve outcome, and should be further studied.